2007
DOI: 10.1016/j.nuclcard.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gated N-13 ammonia PET and gated Tc-99m sestamibi SPECT for quantitative analysis of global and regional left ventricular function

Abstract: Gated N-13 NH(3) PET combined with QGS provides information on both global and regional left ventricular function comparable to that obtained by gated Tc-99m perfusion myocardial SPECT in CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, no previous study systemically compared the accuracy of LV volumes and LVEF measured by GSPECT and GPET, and little information has become available on the differences of LV volumes and LVEF between GSPECT and GPET. 22,23 In our current study, we found that the correlations of LV volumes measurements between GSPECT and GPET were excellent and correlation of LVEF was fair, but the Bland-Altman limits were wider. Therefore, on individual patient's level, GSPECT and GPET-derived functional parameters (especially LV volumes) should not be interchangeable.…”
Section: Effects Of Residual Viable Myocardium On the Accuracy Of LV supporting
confidence: 53%
See 2 more Smart Citations
“…However, no previous study systemically compared the accuracy of LV volumes and LVEF measured by GSPECT and GPET, and little information has become available on the differences of LV volumes and LVEF between GSPECT and GPET. 22,23 In our current study, we found that the correlations of LV volumes measurements between GSPECT and GPET were excellent and correlation of LVEF was fair, but the Bland-Altman limits were wider. Therefore, on individual patient's level, GSPECT and GPET-derived functional parameters (especially LV volumes) should not be interchangeable.…”
Section: Effects Of Residual Viable Myocardium On the Accuracy Of LV supporting
confidence: 53%
“…These findings were different from that in previous studies. 22,23 Kanayama et al 23 found that LVEF did not differ between gated 13 N-NH 3 PET and 99m Tc-MIBI SPECT in CAD patients, and the extent of perfusion defects had no influence on the underestimation of LV volumes determined by GPET, compared with that measured by GSPECT.…”
Section: Effects Of Residual Viable Myocardium On the Accuracy Of LV mentioning
confidence: 96%
See 1 more Smart Citation
“…Left ventricular ejection fraction measured routinely and accurately with N-13 ammonia 9 and Rubidium-82 PET, 1012 is a well-established risk-marker in many clinical settings. Indeed, with short-acting radiotracers such as Rubidium-82, rest, peak hyperemic LVEF and LVEF reserve (stress LVEF minus rest LVEF) can be measured, as opposed to SPECT MPI wherein LVEF is measured on the post-stress images (~15–60 minutes post stress).…”
Section: Pet Mpi Risk Markersmentioning
confidence: 99%
“…Border detection becomes more complicated in apical defects, it has been forced the wall to be a smooth connection between noninfarcted portions of the wall (Faber et al 1999). Finally, positron emission tomography from nuclear studies has been used accurately for global and regional detection of LV function (Kanayama et al 2007). It has given an acceptable result for LV volumes and EF in comparison with MRI and angiography (Schae-fer et al 2003).…”
Section: Introductionmentioning
confidence: 99%